ERA-Interim Project, Monthly Means ... - European Centre For Medium-Range Weather Forecasts (UCAR/NCAR - Research Data Archive, 2012)
ERA-Interim represents a major undertaking by ECMWF (European Centre for Medium-Range Weather Forecasts) to produce a reanalysis with an improved atmospheric model and assimilation system which replaces those used in ERA-40, particularly for the data-rich 1990s and 2000s, and to be continued as an ECMWF Climate Data Assimilation System (ECDAS) until superseded by a new extended reanalysis. Preliminary runs indicated that several of the inaccuracies exhibited by ERA-40 such as too-strong precipitation over oceans from the early 1990s onwards and a too-strong Brewer-Dobson circulation in the stratosphere, were eliminated or significantly reduced. Production of ERA-Interim, from 1989 onwards, began in summer of 2006. (The period 1979-1988 was prepended in 2011.)Through systematic increases of computing power, 4-dimensional variational assimilation (4D-Var) became feasible and part of ECMWF operations since 1997, paving the way to base ERA-Interim on 4D-Var (rather than 3D-Var as in ERA-40). Enhanced computing ...